Design and Application of Vertical Temperature Profile Observation System for Arctic Sea Ice Melt Pond - ZUO Guangyu; DOU Yinke; WU Shunjie; CHANG Xiaomin; KOU Liwei; LI Wenlong; YANG Bo (Taiyuan Ligong Daxue xuebao)
[Purposes] The evolution of the Arctic sea ice melt pond includes the morphological change in the horizontal direction and the structural evolution in the vertical direction, but there is a few observation equipment for the vertical structure of the melt pond. In view of the problems existing in the observation of the Arctic sea ice melt pond, an automatic observation system for the vertical temperature profile of melt pond is designed. [Methods] The system is composed of observation module, power supply module, data acquisition module, data transmission module, and auxiliary module. [Findings] This system can realize continuous automatic observation of the atmosphere, snow, sea ice, melt pond, and upper ocean. The system can also provide on-site data for the verification of the results of the melt pond model, improving China’s ability to observe the rapid changes of the Arctic sea ice, and has important engineering application value.